Duelling with doctors, restoring honour and avoiding shame? A cross-sectional study of sick-listed patients’ experiences of negative healthcare encounters with special reference to feeling wronged and shame - Lynøe, Niels (Journal of medical ethics, 2013)
Aims The aim of this study was to examine if it is plausible to interpret the appearance of shame in a Swedish healthcare setting as a reaction to having one's honour wronged. Methods Using a questionnaire, we studied answers from a sample of long-term sick-listed patients who had experienced negative encounters (n=1628) and of these 64% also felt wronged. We used feeling wronged to examine emotional reactions such as feeling ashamed and made the assumption that feeling shame could be associated with having one's honour wronged. In statistical analyses relative risks (RRs) were computed, adjusting for age, sex, disease-labelling, educational levels, as well as their 95% CI. Results Approximately half of those who had been wronged stated that they also felt shame and of those who felt shame, 93% (CI 91 to 95) felt that they had been wronged. The RR was 4.5 (CI 3.0 to 6.8) for shame when wronged. This can be compared with the other emotional reactions where the RRs were between 1.1 (CI 0.9 to 1.3)-1.4 (CI 1.2 to 1.7). We found no association between country of birth and feeling shame after having experienced negative encounters. Conclusions We found that the RR of feeling shame when wronged was significantly higher compared with other feelings. Along with theoretical considerations, and the specific types of negative encounters associated with shame, the results indicate that our research hypothesis might be plausible. We think that the results deserve to be used as point of departure for future research.